Manufacturing Ceramic Foams at Very High Temperature by the Unconventional Process of Direct Microwave Heating - Lucian Paunescu; Sorin Mircea Axinte; Marius Florin Dragoescu; Felicia Cosmulescu (Newinera Publisher, 2020)
Abstract SiC ceramic foams were manufactured by direct microwave heating up to 1520 ºC. Silicon carbide (42-68 wt.%), quartz sand as a silica supplier (20-38 wt.%), coal fly ash (12-20 wt.%) and a constant water addition of 15 wt.% were used as starting materials. The ceramic foam samples had semi-open microstructures in which neighboring cells are partially connected to each other and partially closed. Due to the very dense cellular walls and the very low cells size (below 21 μm), the compressive strength had very high values (41.3-56.5MPa), the porosity was within an average value range (52.4-57.6%) and the thermal conductivity and the apparent density had relatively high values. In energy terms, the technique of direct microwave heating was very advantageous, the specific energy consumption being very low (1.04-1.21 kWh/kg) compared to the consumptions achieved by conventional methods. The application field of SiC ceramic foams obtained by the bonding method and using silica as a bonding agent includes hot gas or molten metal filters, porous burners, catalytic supports and others. From the four tested experimental variants, it could be concluded that the optimal sample was that achieved at 1520 ºC with 68% silicon carbide, 20% quartz sand, 12% coal fly ash and 15% water addition, having the porosity of 57.6%, thermal conductivity of 0.174 W/m·K, compressive strength of 56.5 MPa and the equivalent pore size between 9-21 μm.